PERANCANGAN BUKU “THE BASIC OF MODERN CALLIGRAPHY WITH BRUSH PEN” - Muhacaca Gobenvy; dini faisal (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
Guidebook of "The Basic of Modern Calligraphy with Brush Pen" is designed with the aim to give a learning media for modern calligraphy enthusiasts to be able to write well starting from basic techniques and give understanding in the scope of modern calligraphy. The method that used in this design is Research and Development (R&D) which begins with data processing, designing a new work system, product testing, and improvement steps. This design will produce a book as the main product and some others media such as: x-banner, poster, guideline notebook, t-shirt, totebag, brush pen pouch, and e-book that have a function as supporting media of the book "The Basic of Modern Calligraphy with Brush Pen".Keywords : Guidebook, Modern Calligraphy, Brush Pen